Factors Affecting Employee Performance At The Office Of The Education and Culture Office Of South Bengkulu Regency - utami, Dahlia Putri; Susanti, Neri; Yanti , Rina Trisna (Universitas Dehasen Bengkulu, 2024)
The aim of this research is to determine the factors that influence employee performance at the education and culture office of South Bengkulu district. This research was conducted on employees of the education and culture office of South Bengkulu district. The population of this research is employees of the education and culture service of South Bengkulu district, while the sample of this research is employees of the education and culture service of South Bengkulu district, totaling 85 people. This means that the sample material uses quantitative methods. Using research test data analysis techniques, the research results can be concluded that respondents' perceptions of Work Quality (X1), Work Quantity (X2), Responsibility (X3) and Cooperation (X4) influence Employee Performance (Y) with multiple linear regression results The following equation is obtained: Y = 1.582 + 0.212 X1 + 0.249X2 +0.229 (X_3) + 0.282 (X_4). The coefficient of determination is R2 = 0.785 or around (78.50%) through hypothesis testing jointly (simultaneously) and individually (partially) in this research using the f test and t test, Quality of Work (X1), Quantity of Work (X2 ), Responsibility (X3) and Cooperation (X4) = 0.000, that means the fsig value < 0.05 shows that together they have significant factors.